Sharing Experiences Together: Within- and Across-Sector Collaboration among Public Preschool Educators. Issue 8 (17th November 2019) - Mowrey, Sascha C.; King, Elizabeth K.
ABSTRACT: Research Findings : The current study explored the patterns of collaboration among early childhood educators in order to understand the extent to which collaborations exist for practitioners, either formally or informally, within and across public preschool, Head Start, and child care sectors in a community and the extent to which work environment factors support or hinder such collaborations. Work environment factors, including paid professional development time, agency in decision-making and educator salaries were examined as contributors to collaboration for lead and assistant teachers. This study used reports from 68 lead teachers, assistant teachers, and other early childhood educators working in public preschool programs. The current study found that collaboration occurs frequently and informally within sites and sectors; however, across-sector collaboration occurs less frequently and more formally. Teachers' agency in decision-making and ability to cover basic living expenses were related to across-sector collaboration among teachers. Practice or Policy : This study has implications for educator professional development, with a specific focus on administrative strategies and policies facilitative of collaboration within sites and sectors as well as across sectors.